Business process reengineering pada sistem administrasi sewa kamar di kota malang - Muhammad Rifki Yohandy; Ilyas Nuryasin (Universitas Muhammadiyah Riau, 2024)
The improvement of operational efficiency in the room rental industry has become a primary focus for stakeholders. This article introduces a study proposing the implementation of Business Process Reengineering (BPR) in the room rental administration system in the city of Malang. The main objective of this research is to identify, analyze, and redesign existing business processes to enhance efficiency in room rental services and management. The methodology involves observation, business process analysis, and the application of BPR principles to adjust the administration system. This study highlights the need for innovation in information technology to support sustainable business process transformation. The results indicate that the implementation of BPR in the room rental administration system can lead to a significant improvement in operational efficiency, accelerating services by 65.397%, as evidenced by the Throughput Efficiency test. This is a notable increase from the previous 26.903% before BPR to 92.30% after BPR. The implications of these findings provide a foundation for further development in integrating the latest technology within the context of the room rental industry.